Biodiesel production from Mazari palm (Nannorrhops ritchiana) seeds oil using Tungstophosphoric acid decorated SnO2@Mn-ZIF bifunctional heterogeneous catalyst - Sahar, J. (Elsevier B.V., 2022)
The aim of this study is to develop novel and an efficient bifunctional heterogeneous catalyst based on the SnO2 @Mn-ZIF core shell support decorated with Tungstophosphoric acid (TPA) active moieties. The designed catalyst was characterized with Thermal Gravimetric analysis (TGA/DTA), X-Ray Diffraction analysis (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDX) analysis, Fourier transform infrared spectroscopy (FT-IR), Brunauer Emmet Teller (BET) analysis and Temperature Programmed Desorption of ammonia (NH3âTPD) and carbon dioxide (CO2âTPD) for structural and morphological investigation. Effect of crucial parameters such as methanol to oil molar ratio, reaction temperature, reaction time, agitation speed and catalyst dosage were thoroughly studied to develop profitable biodiesel process. The results indicated that Tungstophosphoric acid was well dispersed on the surface of the support. Further, it was noted that the catalyst with 30 wt Tungstophosphoric acid onto the support formulation provided maximum biodiesel yield of 91.5 under optimum reaction conditions of 6 wt catalyst dosage with 18:1 methanol to oil molar ratio, 500 rpm stirring speed and reaction temperature of 100 Â°C for 3 h. Finally the designed catalyst experienced profound stability and was recycled up to five times for biodiesel production without any prior treatment. Â© 2022 Elsevier B.V.